Exploring the Impact of User Interface and Service Quality in Enhancing Repurchase Intentions - Dalimunthe, Putri Amini; Suryani, Wan (Universitas Bumigora, 2024)
In this digital era, food delivery services like ShopeeFood are becoming increasingly popular. ShopeeFood plays a crucial role in meeting consumer needs by offering convenience and ease. However, user interface and service quality are critical aspects of the user experience. An inadequate user interface or low service quality can lead to dissatisfaction and influence the user's intention to reuse ShopeeFood. This study aims to determine the influence of user interface (UI) and service quality on the repurchase intention of ShopeeFood users in the Medan Polonia District. The method used a quantitative-descriptive approach. The sample size used is 100 people. The results of this study indicate that the UI has a positive and significant effect on repurchase intention. Moreover, UI and service quality positively and significantly affect repurchase intention. This research contributes valuable insights into the pivotal roles of UI and service quality in shaping the repurchase intention of ShopeeFood users in the Medan Polonia District, underscoring their significance in enhancing user repurchase intention within the digital food delivery sector. Given the increasing reliance on digital platforms for food delivery services, ShopeeFood is a crucial interface for meeting consumer needs for convenience and efficiency. Furthermore, the study emphasizes that the synergistic impact of UI and service quality collectively enhances repurchase intention, offering actionable insights for stakeholders to refine service delivery and maintain competitiveness in the evolving digital marketplace.